(untitled) - Malham, Howell Jr. (San Francisco, CA, 2013)
A smart and witty take on strategy...an essential business topic. Every day, millions of professionals around the world discuss strategy, and they assume that everyone else in the room defines "strategy" the same way. But they don't. Howell J. Malham Jr. has created a book that goes straight to the heart of the issue.
Keywords: Strategic planning,Hoạch định chiến lược